LOW RESISTIVITY PAY DEVELOPMENT: CASE STUDY OF TALANGAKAR FORMATION ASRI BASIN, OFFSHORE SOUTHEAST SUMATRA, INDONESIA - Dwandari Ralanarko; Pranowo Nugroho; Edy Sunardi; Ildrem Syafri; Billy G. Adhiperdana (Marine Geological Institute of Indonesia, 2023)
Southeast Sumatra is a prolific oil and gas block located offshore in the Java Sea, 90 km north of Jakarta Bay. This area covers two major basins, namely Sunda Basin and Asri Basin. The initial development of the area focused on faulted and high closures and high-resistivity reservoirs. Further analysis shows that there are special low-resistivity reservoirs in Widuri Area, especially in the Aryani field. This paper will discuss the low resistivity pay zone reservoirs and fluid containment of the intervals. The paper will also include further assesment this undeveloped interval to increase oil production, considering the upside potential of the reservoirs using current geological, geophysical, and reservoir engineering approaches. Additionally, it will describe the operational challenges faced during the production period. The low-resistivity pay zone, a hydrocarbon-bearing reservoir in the Aryani field of the Widuri area, was identified using gas readings in the daily drilling reports, complemented with mud logging data. The Basal Sand interval, which drapes above the basement, was the site of the first producing well of Basal Sand, Aryani AC-X, preceded by a hydraulic fracturing job. Lambda-mu-rho inversion was implemented to delineate this reservoir. To recognize the potency in those wells, data reconfirmation was conducted between the elan summary, sidewall core, and cutting data. Aryani AC-X has successfully drained oil using a submersible pump, with an initial production of 408 bopd and cumulative production of 240 MBO.